An Analysis of Product Lifetimes in a Technologically Dynamic Industry - Bayus, Barry L. (Management Science, 1998)
The conventional wisdom that product lifetimes are shrinking has important implications for technology management and product planning. However, very limited empirical information on this topic is available. In this paper, product lifetimes are directly measured as the time between product introduction and withdrawal. Statistical analyses of desktop personal computer models introduced between 1974 and 1992 are conducted at various product market levels. Results indicate that (1) product technology and product model lifetimes have not accelerated, and (2) manufacturers have not systematically reduced the life-cycles of products within their lines. Instead, the products of firms that have entered this industry in the more recent years tend to be based on previously existing technology, and, not surprisingly, these products have lifetimes that are shorter than those of established firms. Implications of these findings are discussed.